Relevansi Rasulullah sebagai Pendidik Ideal dalam Konteks Masjid sebagai Pusat Pendidikan di Era Modern - Dari, Yuni Wulan; Zalnur, Muhammad; Masyhudi, Fauza (ALSYS, 2024)
The existence of mosques in this modern era has many benefits, especially in the fields of worship and science. This can be seen from the many uses of mosques as gathering places for Muslims in terms of disseminating religious knowledge. This article aims to determine the relevance of the Prophet as an ideal educator in the context of mosques as educational centers in the modern era. This research uses a historical approach which is specifically used as an analysis tool for information or events in the past. The method used in this article is library research, namely using library materials as the main data source intended to explore the theories and concepts of previous experts. The discussion of this article is that the Prophet Muhammad as an ideal educator is one of the main figures in terms of education that we experience today. The spread of education carried out by the Prophet was gradual, from covert to overt. The Prophet carried out educational processes in kuttabs and mosques. In this modern era, the existence of mosques is very important for Muslims. Not only as a place of worship but also as a place for the transformation of religious knowledge.